Role of bicarbonate and volume therapy in the prevention of acute kidney injury in rhabdomyolysis: a retrospective propensity score-matched cohort study - Hye Won Kim; Sejoong Kim; Jung Hun Ohn; Nak-Hyun Kim; Jongchan Lee; Eun Sun Kim; Yejee Lim; Jae Ho Cho; Hee Sun Park; Jiwon Ryu; Sun-wook Kim (The Korean Society of Nephrology, 2022)
Background Although bicarbonate has traditionally been used to treat patients with rhabdomyolysis at high risk of acute kidney injury (AKI), it is unclear whether this is beneficial. This study compared bicarbonate therapy to non-bicarbonate therapy for the prevention of AKI and mortality in rhabdomyolysis patients. Methods In a propensity score-matched cohort study, patients with a creatine kinase (CK) level of >1,000 U/L during hospitalization were divided into bicarbonate and non-bicarbonate groups. Patients were subgrouped based on low-volume (<3 mL/kg/hr) or high-volume (≥3 mL/kg/hr) fluid resuscitation in the first 72 hours. Logistic regression analyses were used to identify the impacts of bicarbonate use and fluid resuscitation on AKI risk and need for dialysis. The Kaplan-Meier method was used to estimate survival. Volume overload and electrolyte imbalances were assessed. Results Among 4,077 patients, we assembled a cohort of 887 pairs of patients treated with and without bicarbonate. Bicarbonate group had a higher incidence of AKI, higher rate of dialysis dependency, higher 30-day mortality, and longer hospital stay than the non-bicarbonate group. Further, patients who received high-volume fluid therapy had worse renal outcomes and a higher mortality than those who received low-volume fluids regardless of bicarbonate use. Bicarbonate use, volume overload, and AKI were associated with higher mortality. Volume overload was significantly higher in the bicarbonate group than in the non-bicarbonate group. Conclusion Bicarbonate or high-volume fluid therapy for patients with rhabdomyolysis did not reduce AKI or improve mortality compared to non-bicarbonate or low-volume fluid therapy. Limited use of bicarbonate and adjustment of fluid volume may improve the short- and long-term outcomes of patients with rhabdomyolysis.